Subnational Training on Use of the Kenya Meteorological Department’s ENACTS Maprooms: Central Kenya - Ruirie, Onesmus; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Improved availability and quality of climate data and information has been necessary but not sufficient in the development of effective, decision-relevant, sustainable, and locally-led climate services for the agricultural sector in Kenya. In particular, while the Kenya Meteorological Department (KMD) has long produced high quality information available at high resolution, this has not been enough to ensure that it is easily accessed, understood, or able to be used at the sectoral level in decisionmaking for agriculture. Rather, intentional efforts to both promote the translation (contextualization) and transfer (communication) of this information alongside capacity building for its use have been needed. An important platform for facilitating the access and wider use of climate information in decisionmaking by governments, as well as the public and private sectors, is the IRI’s Climate Data Library. The Data Library is a powerful and freely accessible online platform that allows users to view, analyse, download, and share hundreds of terabytes of multidisciplinary climate-related data through a standard web browser (Blumenthal et al., 2014). ICT solutions like this and especially co-created map visualizations such as the IRI’s interactive “Maproom” visuals and graphs of climate data can play a large role in making climate information more usable by translating past, present, or future conditions into expected impacts and management advisories for different decision-makers (Christel et al., 2018; Daron et al., 2015).